Legal Protection for Consumers' Personal Data in Online Shopping - Mawarni Karim; Fenty U. Puluhulawa; Jufryanto Puluhulawa; Vifi Swarianata (Estudiante Law Journal, 2022)
In the current technological era, developments occur in all aspects of life including trading activities, namely online shopping. Online shopping began to grow and develop into a habit for the community. Mothers' shopping habits are increasingly turning to buying and selling online for more practical reasons. For modern society, especially in Indonesia, online shopping, online shopping applications, and social media have various kinds of goods or services that they want or need. the purpose of conducting this research is to analyze the legal protection of the personal data of consumers who shop online. The research used in this paper is Juridical Sociological research and uses a descriptive qualitative research approach and uses interactive analysis techniques